Foresting Entrepreneurial Spirit of Santri With Santripreneur Academy Program: Study on Pesantrenpreneur Mukmin Mandiri - Bagus Setiawan, Heri Cahyo; Hidayat, Nur; Kurniawan, Aries; Komara, Beni Dwi (Journal of Islamic Economics Perspectives, 2022)
Currently, pesantren must be able to produce graduates with various skills because not all outputs or alumni become scholars or kiai. One of the educations that are provided for students is entrepreneurship. This study will present an overview of how the efforts of Islamic boarding schools not only provide students with understanding religious knowledge (tafqquh-fiddin), but are taught about skills that can have economic value with entrepreneurship education. The Mukmin Mandiri Islamic Boarding School in Sidoarjo is the object of this research, in which students are taught religious knowledge and at the same time understand economics and business through the Santripreneur Academy program. The purpose of exploring and exploring the role of the entrepreneurship education program which is named the Santripreneur Academy program is interesting to answer the research question "how to grow an entrepreneurial or entrepreneurial spirit for students through the santripreneur academy program?". The research method uses an exploratory qualitative method with santri informants and the management of the Santripreneur Academy program at the Mukmin Mandiri Islamic Boarding School. In-depth interviews are something that must be done to explore and then analyze to answer the research questions that have been asked. As for the results of this study, there are three important things that are felt by the entrepreneurial spirit, including; entrepreneurship education, entrepreneurial motivation and entrepreneurial knowledge that encourage him to prepare himself to become an entrepreneur. The details can be read further in the research results in this article.